La critica heideggeriana all’umanismo e la tecnica: per un decentramento dell’umano al tempo dell’antropocene - Agnello, Chiara (Mechane, 2022)
The context in which Heidegger’s technique is represented as the ultimate achievement of modern metaphysics is the same in which the critique of humanism of the metaphysical tradition matures, but above all in which the perspective of decentralization of the human to the detriment of any residual anthropology emerges with ever greater clarity. This overall critical vision is inscribed in the broader context in which the question of technique is posed with the Kehre on an ontological and not anthropological basis on the basis of the new formulation of the Seinsfrage. The rethinking of the essence of the human starting from the difference from the other, from an otherness that man does not have, has considerable consequences also on a hypothesis of reconsidering the technique that profitable configures the beyond-humanistic horizon. Accepting the invitation to overcome all anthropologism and subjectivism in the perspective that precisely by virtue of such decentralization man is not master of the entities that surround him, it seems that today more than ever it can represent a fundamental hub for thinking about our future on the planet.